2012
DOI: 10.4137/bii.s8933
|View full text |Cite
|
Sign up to set email alerts
|

Binary Classifiers and Latent Sequence Models for Emotion Detection in Suicide Notes

Abstract: This paper describes the National Research Council of Canada’s submission to the 2011 i2b2 NLP challenge on the detection of emotions in suicide notes. In this task, each sentence of a suicide note is annotated with zero or more emotions, making it a multi-label sentence classification task. We employ two distinct large-margin models capable of handling multiple labels. The first uses one classifier per emotion, and is built to simplify label balance issues and to allow extremely fast development. This approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 24 publications
0
38
0
3
Order By: Relevance
“…Since the other teams (Cherry, Mohammad and De Bruijn 2012;Luyckx et al 2012;McCart et al 2012;Spasić et al 2012) reported details of their algorithms and outcomes, the shared task also provides insights into the techniques that did not produce satisfactory results. For example, Yu et al (2012) reported low accuracy using Wordnet, character n-grams and word n-grams (a contiguous sequence of n terms).…”
Section: Evaluating Labeling Systemsmentioning
confidence: 99%
“…Since the other teams (Cherry, Mohammad and De Bruijn 2012;Luyckx et al 2012;McCart et al 2012;Spasić et al 2012) reported details of their algorithms and outcomes, the shared task also provides insights into the techniques that did not produce satisfactory results. For example, Yu et al (2012) reported low accuracy using Wordnet, character n-grams and word n-grams (a contiguous sequence of n terms).…”
Section: Evaluating Labeling Systemsmentioning
confidence: 99%
“…On the other hand, we are working on a project that aims to prevent suicide using social networks (Facebook, Twitter, forums, etc.). Cases of suicides have been reported in recent years as people have posted on social networks expressing their thought or addressing messages to their families (Cherry et al, 2012). We believe that sentiment and emotion analysis can be adapted to detect dysphoric states.…”
Section: Resultsmentioning
confidence: 99%
“…Four machine learning algorithms were found to perform well in this problem space: support vector machines (SVM) (Alm et al, 2005;Aman & Szpakowicz, 2007;Brooks et al, 2013;Cherry et al, 2012), Bayesian networks (Sohn et al, 2012;Strapparava & Mihalcea, 2008), decision trees , and k-nearest neighbor (KNN) Holzman & Pottenger, 2003). The features were held constant across different classifiers in the candidate set.…”
Section: Machine Learning Experimentsmentioning
confidence: 99%